2019
DOI: 10.1080/19476337.2019.1661878
|View full text |Cite
|
Sign up to set email alerts
|

Development of low-fat fried fish using a two-prong strategy

Abstract: In this study, a two-prong strategy was devised to reduce fat-uptake in deep-fat fried fish by developing a low cost, sustainable and product-friendly edible coating using fish processing byproducts and replacement of corn starch in batter with sweet potato starch. Edible coatings (protein concentrations of 0, 5%, 10%, and 15%) were prepared from fish protein isolates using isoelectric solubilization and precipitation. Coating with 15% protein and sweet potato starch-based batter resulted in the highest reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In another research, it was explained that the less oil absorption in the coated products may be related to the formation of covalent links within the coatings during frying. 10 In uncoated strips, the water escape might have created pores and channels, 24 thus enhancing the oil absorption, but in the case of coated strips, these pores and channels might have been blocked to prevent moisture loss, thus eventually preventing the fat uptake into the coated product during deep-fat frying. In addition to this, 25 it was proved that the gelation of the protein depends on the structural uniqueness of the protein (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…In another research, it was explained that the less oil absorption in the coated products may be related to the formation of covalent links within the coatings during frying. 10 In uncoated strips, the water escape might have created pores and channels, 24 thus enhancing the oil absorption, but in the case of coated strips, these pores and channels might have been blocked to prevent moisture loss, thus eventually preventing the fat uptake into the coated product during deep-fat frying. In addition to this, 25 it was proved that the gelation of the protein depends on the structural uniqueness of the protein (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…In their report, they found that edible coating containing 15% was able to effectively reduce fat uptake by 60% when compared to the control. Similarly, Azahrani et al (2019) applied the same strategy, although they used a different food matrix (in this case fish) and a hydrocolloid‐based batter system to achieve a much higher reduction in fat uptake and moisture loss.…”
Section: Introductionmentioning
confidence: 99%
“…However, protein-based films gained interest due to their superior mechanical properties. Our previous research showed that the application of an edible coating prepared from protein recovered from fish and chicken processing byproducts results in a significant reduction in fat uptake in deep-fat-fried products [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%